Advances in Heart Electrotherapy - Lewicka, Ewa; Dąbrowska-Kugacka, Alicja; Liżewska-Springer, Aleksandra (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The introduction of permanent cardiac pacing in the late 1950s began the era of cardiac electrotherapy. In the 1980s, implantable cardioverter defibrillators (ICDs) were introduced. These advances created new challenges for cardiac implantable electronic devices (CIEDs). Right ventricular pacing was the primary breakthrough; however, over the years, it has become apparent that it can induce cardiac contraction dyssynchrony. Biventricular pacing allowed for the alleviation of dyssynchrony and improved the survival of patients with heart failure and bundle branch block. In recent decades, His bundle pacing has become a new strategy for physiological ventricular activation. However, the use of CIEDs carries several risks, e.g., complications related to transvenous leads. This led to the development of percutaneous lead extraction techniques as well as the introduction of a subcutaneous ICD (S-ICD) and leadless pacing. Technological evolution promises an exciting future in the development of cardiac electrotherapy.In this Special Issue, readers can find out about the clinical and hemodynamic aspects of right ventricular, His bundle, and biventricular pacing; ICD therapy; treatment of complications and technological advances in cardiac electrotherapy.